FloGARCH: Realizing long memory and asymmetries in returns volatility - Harry Vander Elst (National Bank of Belgium, 2015)
We introduce the class of FloGARCH models in this paper. FloGARCH models provide a parsimonious joint model for low frequency returns and realized measures and are sufficiently flexible to capture long memory as well as asymmetries related to leverage effects. We analyze the performances of the models in a realistic numerical study and on the basis of a data set composed of 65 equities. Using more than 10 years of high-frequency transactions, we document significant statistical gains related to the FloGARCH models in terms of in-sample fit, out-of-sample fit and forecasting accuracy compared to classical and Realized GARCH models.
Keywords: C22; C53; C58; G17; 330; Realized GARCH models; high-frequency data; long memory; realized measures.; Aktie; ARCH-Modell; Zeitreihenanalyse; Maximum-Likelihood-Schätzung